CAN VISUAL MEDIA IMPROVE PROBLEM SOLVING ABILITIES OF ELEMENTARY STUDENTS ON GEOMETRY? - Umar Umar; Mohammad Archi Maulyda (Universitas Muhammadiyah Semarang, 2021)
The aims of this study were (1) to reveal the students 'ability to solve problems related to the area of the flat shape that was taught after using the Problem Based Learning model supported by visual media, (2) to reveal the students' ability to solve problems related to the area of the flat shape that was taught after using the Direct Instruction model supported by visual media, (3) to reveal whether there is an effect of the Problem Based Learning model supported by visual media on the ability to solve problems related to the area of a flat shape. This study uses a research design Nonequivalent Control Group Design with Quasi Experiment research techniques or quasi-experimental with a quantitative approach. The subjects of this study were fifth grade students of SDN Senurus. The data analysis used in this study was the One Sample T Test and the Independent Sample T Test. The conclusions of the results of this study are, (1) the ability to solve problems related to the area of the flat shape of the fifth grade students of SDN Senurus using the Problem Based Learning learning model supported by visual media, the results of the calculations obtained a significant value of 0.000 and a significant level of 5% which means the significance value is 0.000 <0.05 and the student's average score was 86.24, (2) the student's ability to solve problems related to the area of a flat shape using the Direct Instruction model supported by visual media, the results of the calculation obtained a significant value of 1,000 and with a significant level of 5% which means the value the significance is 1,000> 0.05 and the student's average score is 75.00, (3) there is an effect of the Problem Based Learning model supported by visual media on the ability to solve problems related to the area of the flat shape of class V SDN Senurus is proven by showing a significant value of 0.000 with the level 5% significant so there is a significant effect